A comparative analysis of metadata best practices and guidelines: issues and implications. (2015) - Park, Jung-Ran; Brenza, Andrew; Lu, Caimei
Through a comparative analysis of local institutions' metadata guidelines based on Dublin Core (DC) metadata, the study examines variations and commonalities in terms of metadata usage and naming conventions and the usage of refinement qualifiers and encoding standards. The study also examines the influence of subject domain and resource type in naming conventions. The study results evince divergence across metadata guidelines especially designed for resource and domain specific repositories. The naming conventions indicate that DC metadata semantics may be too broad to describe the characteristics of domain and resource specific repositories, unlike cross-domain and heterogeneous resource types. The employment of a high number of refinement qualifiers may engender a higher degree of semantic specificity for describing heterogeneous resource types. The study provides insights into metadata semantics in relation to resource type, subject domain, and refinement qualifiers. The study also brings forth insights for metadata planning, quality control, and interoperability.